The Influence of School Principal Leadership Immediately with Congregational Spirituality for Strengthening The Character of Teachers and Students - Dasrimin, Henderikus (Journal of Asian Orientation in Theology, 2025)
This research aims to describe the implementation of school principal leadership that is imbued with the spirituality of religious congregations in an effort to strengthen the character of teachers and students. The research method used is a qualitative descriptive approach. The research design used a multi-site study, which was carried out in three Catholic Junior High Schools (in Indonesian it is abbreviated: SMPK), in Malang City, Indonesia. The three schools are SMPK Mardi Wiyata Malang, SMPK Santa Maria 2 Malang, and SMPK Sang Timur Malang. The results of the research show that the implementation of school principal leadership that is imbued with congregational spirituality is developed through a spirituality of a loving heart, a spirituality of the heart that upholds human honor and dignity, and a spirituality of a caring heart. The application of spiritual leadership can have a positive impact on the personal formation of teachers and employees as well as strengthening the character of students.